OUTBREAKS AND EPIDEMICS : Battling infection from measles to coronavirus - Senthilingam, Meera (London : Icon Books Ltd, 2020)
In recent years, outbreaks of Ebola and Zika have provided vivid examples of how difficult it is to contain an infection once it strikes, and the panic that a rapidly spreading epidemic can ignite. But while we chase the diseases we are already aware of, new ones are constantly emerging, like the coronavirus that spread across the world in 2020. At the same time, antimicrobial resistance is harnessing infections that we once knew how to control, enabling them to thrive once more.
Includes bibliographical references and index.
Keywords: COVID-19 (Disease).; Epidemics -- History; Communicable diseases -- History